Analysis of Factors Affecting the Well-Being of the Elderly in Bengkulu City - Yesi Septriani; Azansyah (Asian Journal of Applied Business and Management, 2024)
Well-being is a broad concept that has many factors that can influence it. One indicator that reflects the success of development is the increase in life expectancy (UHH) of the population, which also has an impact on the increasing number of elderly people. This study aims to analyze the factors that affect the welfare of the elderly in the city of Bengkulu. The influence of education level, employment status, income, marital status, and health access to the welfare of the elderly in Bengkulu City. The sample size was 100 elderly people out of a total of 31,857. Samples obtained from the calculation of the number of elderly population in Bengkulu using Slovin formula and error rate of 10%. Data collection was conducted through the dissemination of questionnaires, structural interviews and in-depth interviews. Analyzed by logistic regression analysis. Based on the results of the study, the level of education, employment Status, marital Status and Health Access does not affect the welfare of the elderly and income significantly and positively affect the welfare of the elderly in the city of Bengkulu.